High-efficiency two-stage LED driver with integrated PFC and LLC resonant converter for public lighting - Marref Mohammed Amine; Seyf Eddine Bechekir; Mokhtaria Jbilou; Mostefa Brahami; Abdelber Bendaoud (Institute of Advanced Engineering and Science, 2026)
This paper presents the design, implementation, and experimental validation of a 150 W two-stage light-emitting diode (LED) driver integrating a power factor correction (PFC) stage and a half-bridge LLC resonant converter for public lighting applications. The problem addressed is the insufficient power quality, limited efficiency, and poor harmonic performance of conventional LED drivers used in street lighting. The proposed method combines an advanced PFC front-end with an LLC resonant converter optimized using first harmonic approximation (FHA) to achieve high efficiency, stable output regulation, and soft-switching operation. Experimental results demonstrate a significant improvement in power quality, with the input current total harmonic distortion (THD) reduced from 134% to 17%, a near-unity power factor, a regulated LED output of 31.6 V/4.72 A, and a conversion efficiency exceeding 95%. The significance of this work lies in providing a high-performance, standards-compliant driver that supports reliable, energy-efficient, and grid-friendly public lighting with reduced operational costs.